Optical Coherence Tomography Angiography-Based Quantitative Assessment of Morphologic Changes in Active Myopic Choroidal Neovascularization During Anti-vascular Endothelial Growth Factor Therapy - Wang, Yao; Hu, Zhongli; Zhu, Tiepei; Su, Zhitao; Fang, Xiaoyun; Lin, Jijian; Chen, Zhiqing; Su, Zhaoan; Ye, Panpan; Ma, Jian; Zhang, Li; Li, Jinyu; et al. (Frontiers in Medicine, 2021)
Purpose: To establish quantitative profile of the morphologic changes among patients with active myopic choroidal neovascularization (mCNV) before and after anti-vascular endothelial growth factor (VEGF) therapy using optical coherence tomography angiography (OCTA) to assess the therapeutic response. Methods: Patients with active mCNV who received anti-VEGF injections between February 2017 to October 2020 and fit the study criteria were retrospectively reviewed. Quantitative analysis of their OCTA images were carried out to evaluate the morphologic features and vascular changes of mCNV lesions in response to anti-VEGF therapy. For further quantitative profiling, mCNV area, fractal dimension, vessel area, vessel density, vessel diameter, vessel length, vessel junction, junction density and vessel tortuosity were obtained by means of advanced skeletonization postprocessing analyses. Results: 31 eyes of 29 consecutive patients with OCTA-positive mCNV lesions (mean spherical equivalent: -12.55 ± 3.24 diopters) were included. The 31 cases were divided into two phenotypes at baseline: organized interlacing pattern (83.87%) and disorganized vascular loops pattern (16.13%). The values of mCNV area, fractal dimension, vessel area, vessel length, vessel junction and junction density decreased remarkably one month after the initial anti-VEGF injection (p < 0.001). Although vessel density, vessel diameter and vessel tortuosity increased meanwhile, only vessel diameter displayed statistical significance (p = 0.027). Of note, relative ratio analysis showed that vessel junction was the most sensitive biomarker in response to anti-VEGF therapy, reflecting a mean decrease of 50.36%. Sensitivity lowered successively in biomarkers of vessel length, vessel area, junction density, mCNV area and fractal dimension. In addition, percent change of mCNV area (r = 0.552, p = 0.002), fractal dimension (r = 0.446, p = 0.017), vessel area (r = 0.518, p = 0.005) and vessel length (r = 0.440, p = 0.019) were moderately associated with that of central retinal thickness. Conclusions: The study showed morphological as well as quantitative changes on OCTA responding to anti-VEGF treatment in mCNV patients, among which vessel junctions might be the most predictive biomarker. OCTA-based analysis, providing intuitive images and a large spectrum of quantitative data at the same time, could promote new insights into the therapeutic response assessment in mCNV patients.